A novel systematic, risk based approach to support the designation of aquatic disposal sites - Lonsdale, Jemma-Anne; Blake, Sylvia; Griffith, Andrew (Marine pollution bulletin, 2021)
Humans rely fundamentally on the marine environment, which is at the same time subject to an increasingly broad range of anthropogenic pressures, leading to growing concerns and the need for effective management for marine protection. One activity is the dredging of ports and harbours which is necessary to maintain safe channels for commercial and recreational navigation. Regulatory authorities in developing countries have few resources to conduct full EIAs for determining dredged material disposal sites but are required to do so under international obligations. The Tool in this paper provides an effective, pragmatic, transparent, consistent, and robust approach to protect the environment whilst using limited technical and scientific resources through a risk based approach to defining need, characterising and designating disposal sites at sea for dredged material. Whilst this approach for dredged material disposal sites was developed for use in UK, this process is equally applicable to other waste types, worldwide.